A comparison of drug‐eluting stent and coronary artery bypass grafting in mildly to moderately ischemic heart failure. (22nd February 2022) - Wang, Kun; Wang, Le; Cong, Hongliang; Zhang, Jingxia; Hu, Yuecheng; Zhang, Yingyi; Zhang, Rui; Li, Wenyu; Qi, Wei
Abstract: Aims: The best revascularization strategy for patients with ischaemic heart failure (IHF) remains unclear. Current evidence and guidelines mainly focus on patients with severe ischaemic heart failure (ejection fraction [EF] < 35%). There are limited data comparing clinical outcomes of coronary artery bypass grafting (CABG) with implantation of drug‐eluting stents (DESs) in patients with mild to moderate ischaemic heart failure (EF 35–50%). It is therefore unknown whether percutaneous coronary intervention (PCI) with DES implantation can provide comparable outcomes to CABG in these patients. Methods and results: From January 2016 to December 2017, we enrolled patients with mildly to moderately reduced EF (35–50%) who had undergone PCI with DESs or CABG. Patients with a history of CABG, presented with acute ST‐elevation myocardial infarction (MI) or acute heart failure, and patients who had undergone CABG concomitant valvular or aortic surgery were excluded. Propensity score‐matching analysis was performed between the two groups. Kaplan–Meier analysis and multivariate Cox proportional hazard regression were applied to assess all‐cause mortality and individual end points. A total of 2050 patients (1330 PCIs and 720 CABGs) were included, and median follow‐up was 45 months (interquartile range 40 to 54). There were significant differences in all‐cause death between the two groups: 77 patients in the PCI group and 27 in the CABG group (DES vs. CABG: 5.8% vs. 3.8%, P = 0.045). After propensity score matching for the entire population, 601 matched pairs were obtained. The long‐term cumulative rate of all‐cause death was significantly different between the two groups (DES vs. CABG: 5.8% vs. 2.7%, P = 0.006). No differences were found in the rates of cardiac death (DES vs. CABG: 4.8% vs. 3.0%, P = 0.096), recurrent MI (DES vs. CABG: 4.0% vs. 2.8%, P = 0.234), and stroke (DES vs. CABG: 6.8% vs. 5.2%, P = 0.163). The rate of repeat coronary revascularization was significantly higher in the PCI group than in the CABG group (12.1% vs. 6.0%, P = 0.000). Conclusions: Considering the higher long‐term survival rate and lower repeat‐revascularization rate, CABG may be superior to DES implantation in patients with mildly to moderately reduced EF (35–50%) and significant CAD.